Analisis Partisipatif terhadap Tantangan dan Peluang Petani Talas di Kabupaten Bogor - Eka Maulidiya, Sherly; Suwandi, Syifa Damaianti; Irfany, Mohammad Iqbal; Rahmawati, Nur Fajri; Amirah, Nurul; Oktaviona, Winda; Alghifari, Ahmad Fadli; Cahyaningrum, Laeli Dyah Tantri; Santosa, Edi (Jurnal Pusat Inovasi Masyarakat, 2025)
Taro (Colocasia esculenta) as a leading commodity in Bogor Regency faces challenges in technology adoption, price fluctuations, and post-harvest infrastructure, so a participatory approach such as a Focus Group Discussion (FGD) is needed to formulate innovative and applicable solutions. This FGD activity aims to identify challenges, opportunities, and strategic solutions for taro farmers in Bogor Regency. Bogor taro is one of the leading commodities with high economic potential, both for the local market and for export. However, farmers face various challenges, such as low adoption of modern technology, price fluctuations, limited access to capital, weak farmer group organizations, and pest and disease attacks. The FGD was carried out in several stages, namely preparation, group discussion, data analysis, and follow-up. The FGD involved 29 participants consisting of taro farmers with diverse profiles based on age, education, farming experience, and land area. The results of the FGD showed several opportunities, such as the development of taro-based processed products, organic farming practices, and export potential. The proposed strategic solutions included technical training to increase productivity, diversification of processed products, government policy support, and strengthening the role of women and youth in farming. The results of this activity are expected to serve as a guide for stakeholders to promote the sustainability and development of the taro farming sector in Bogor Regency.